Advances and applications of wind engineering in exceptional terrain - Jiawu Li; Shucheng Yang; Jianming Hao; Guangzhong Gao; Feng Wang; Hua Bai; Guohui Zhao; Yu Li; Xiaofeng Xue (Journal of Traffic and Transportation Engineering (English ed. Online))
Wind engineering has made significant strides in addressing the challenges posed by exceptional terrains, where traditional methodologies often fall short. This paper reviews the advances in wind tunnel technology and computational fluid dynamics (CFD) that have revolutionized the understanding and prediction of wind effects on bridges, particularly in complex environments. The integration of advanced measurement techniques with wind tunnel experiments has provided deeper insights into wind characteristics, leading to more accurate aerodynamic designs for bridges. The application of these technologies in unique terrains has been instrumental in ensuring the safety and stability of critical infrastructures. The paper reviews the importance of continuous research and collaboration in wind engineering to address the evolving demands of infrastructure in challenging terrains. The article also introduces the wind tunnel facilities at Chang'an University, detailing their capabilities and contributions to research in wind engineering, including the study of aerodynamic performance and control measures for bridges. It is concluded by reflecting on the research team's 20-year journey at Chang'an University, noting their growth, achievements, and contributions to the field of wind engineering.